The “dancing body” on the perceptual frontiers of “telepresence”. Seuil-lab Laboratory - Fritz, Vivian (Revista Eletrônica MAPA D2 - Mapa e Programa de Artes em Dança (e Performance) Digital, 2014)
“Dance is an art derived from life itself, since it is nothing more nor less than the action of the whole human body; but an action transposed into a world, into a sort of space-time, which is no longer quite the same as that of everyday life”. Paul Valéry